2009
DOI: 10.1016/j.mcn.2009.09.008
|View full text |Cite
|
Sign up to set email alerts
|

LGI1-associated epilepsy through altered ADAM23-dependent neuronal morphology

Abstract: Most epilepsy genes encode ion channels, but the LGI1 gene responsible for Autosomal Dominant Partial Epilepsy with Auditory Features produces a secreted protein.LGI1 is suggested to regulate PSD-95 via ADAM22. However, no unbiased screen of LGI1 action has been conducted. Here, we searched for brain genes supporting high affinity LGI-1 binding. ADAM23 was the only LGI1 interactor identified. The related proteins, ADAM22 and ADAM11, but not ADAM12, bind LGI1. Neither ADAM23 nor ADAM11, nor some forms of ADAM22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
2
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(95 citation statements)
references
References 30 publications
4
87
2
2
Order By: Relevance
“…PSD-95, which directly interacts with one major ADAM22 isoform with a PDZ-binding motif (8), was also coimmunoprecipitated with ADAM22 and ADAM23 in wild-type mouse brain. A recent study revealed that ADAM23 mRNA does not express in granule cells of the hippocampal dentate gyrus (12). Our immunohistochemical analysis showed that ADAM23 protein localizes in the outer molecular layers of the dentate gyrus (Fig.…”
Section: Resultsmentioning
confidence: 57%
See 3 more Smart Citations
“…PSD-95, which directly interacts with one major ADAM22 isoform with a PDZ-binding motif (8), was also coimmunoprecipitated with ADAM22 and ADAM23 in wild-type mouse brain. A recent study revealed that ADAM23 mRNA does not express in granule cells of the hippocampal dentate gyrus (12). Our immunohistochemical analysis showed that ADAM23 protein localizes in the outer molecular layers of the dentate gyrus (Fig.…”
Section: Resultsmentioning
confidence: 57%
“…Consistently, LGI1 directly bound to both ADAM22 and ADAM23 in vitro ( Fig. S2A) (8,12,13). Furthermore, to identify overall constituents of the LGI1 complex including indirect interactions, we conducted large-scale purification combined with shotgun proteomic analysis.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…LGI1 mutations cause ADTLE in humans and recent studies have shown that the interaction of LGI1 with ADAM22 has profound effects on synaptic transmission and dendritic maturation (Owuor et al, 2009;Zhou et al, 2009). Interestingly, analysis of NgR1 nulls has revealed that NgR1 also functions at central synapses (McGee et al, 2005;Lee et al, 2008).…”
Section: Ngr1 and Adam22 Associate To Form An Lgi1 Binding Complexmentioning
confidence: 99%